Det 6te almindelige svenske Laudbrugsmøde i Lidkøping fra 15-19de August d. A. - Jørgensen, B. S. (Tidsskrift for Landøkonomi, 2018)
Det 6te almindelige svenske Laudbrugsmøde i Lidkøping fra 15-19de August d. A.